Perbandingan screen-time berdasarkan kuantitas dan kualitas tidur mahasiswa Fakultas Kedokteran Universitas Pembangunan Nasional Veteran Jakarta pada pandemi Corona Virus Disease-19 - Dhea Faizia Tasya; Nurfitri Bustamam; Winda Lestari (Jurnal Kedokteran Syiah Kuala, 2021)
The study result showed that in the pandemic of COVID-19 there was an increase in screen-time that caused sleep disturbances. The Faculty of Medicine Universitas Pembangunan Nasional Veteran Jakarta (FMUPNVJ) implemented the online learning method to prevent transmission of COVID-19. The average of screen-time scheduled for the seventh semester FMUPNVJ was 6.4 hours/day. This study aimed to compare the screen-time based on sleep quantity and quality of FMUPNVJ students. The study used a cross-sectional design with a sample size of 123 subjects. The instruments of this study were the Pittsburgh Sleep Quality Index (PSQI) questionnaire to measure sleep quantity and quality, and a self-reported questionnaire to measure screen-time. The study results showed that most (78.9%) of the subjects were female, aged 21 (20-22) years old with an average of screen-time 10.48 ± 2.87 hours/day, 61% of the subjects had short sleep quantity, and 56.9% of the subjects had poor sleep quality. The results of the statistical test showed that there were differences in screen-time based on sleep quantity (p = 0.000) and sleep quality (p = 0.000). Subjects with high screen-time had short sleep quantity and poor sleep quality.